Engagement and Life Satisfaction: Testing the Parallel Mediator of Academic Engagement Among Muslim Students - Susilawati, Susilawati; Sugiharto, Dwi Yuwono Puji; Sunawan, Sunawan; Awalya, Awalya (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
Student life satisfaction is a determining variable in academic success influenced by student engagement and academic engagement. However, these two seem overlap, yet are actually distinct. This Study aimed to examine how each type of engagement contributes to students life satisfaction. To do so, 524 students of Madrasah Aliyah or Islamic Senior High Schools in Indonesia, aged 15 to 18 years were observed. Their data were collected using three validated instruments, including the Student’s Life Satisfaction Scale, the Student Engagement Scale and the Utrecht Work Engagement Scale (UWES-9S). In the analysis, hierarchical regression and Sobel's test were used. Based on the analysis, it was found that the contribution of emotional engagement dimension and the absorption dimension resulted a significant positive correlation with student’s life satisfaction (p < .01), emotional engagement (β = .440, p < .01) and absorption (β = .966, p < .01). Those directly predicted life satisfaction. In addition, parallel mediation of absorption academic engagement fully mediated the relationship between behavioral engagement and student’s life satisfaction (β = .096, z = 3.38, p < .05) and cognitive engagement and student’s life satisfaction (β = .156, z = 4.05, p < .01). In addition, absorption partially mediated the relationship between emotional engagement and student’s life satisfaction (β = .210, z = 6.90, p < .01). In conclusion, student engagement and academic engagement are not overlapping, but are distinct constructs